Drug Resistance in Toxoplasma gondii - Montazeri, Mahbobeh; Mehrzadi, Saeed; Sharif, Mehdi; Sarvi, Shahabeddin; Tanzifi, Asal; Aghayan, Sargis A.; Daryani, Ahmad (Frontiers in Microbiology, 2018)
Toxoplasma gondii (T. gondii) is a global protozoan parasite infecting up to one-third of the world population. The most widely used drugs for treatment of toxoplasmosis are pyrimethamine (PYR) and sulfadiazine (SDZ); however, several failure cases have been recorded as well; suggesting the existence of drug resistant strains. In this systematic review, the data was collected from six English data bases (PubMed, Science Direct, Scopus, Google Scholar, ISI Web of Science and EBSCO) to evaluate drug resistance in T. gondii including in vitro and in vivo studies. Results of the present review were 34 research papers evaluated 37 drugs and compounds and more than 100 resistant strains of T. gondii during 1977- February 2017. In 12 surveys, T. gondii mutants were identified as a good model to study mechanisms of resistance and drug target in parasites. Interestingly, analogous amino acid substitutions in the Toxoplasma enzyme identified to confer PYR resistance. Moreover, resistance to clindamycin, spiramycin and azithromycin is encoded in the rRNA genes of T. gondii. However, T. gondii SDZ resistance mechanism has not been proved yet. As the only worrying trend is a very slight recent increase in the SDZ resistance, most of the studies were carried out using SDZ. Six resistance strains to SDZ were found in clinical cases between 2013 and 2017. Among them the Brazilian T. gondii isolates, of TgCTBr11, Ck3 and Pg1 were identified in human toxoplasmosis, as well as in livestock intended for human consumption. In conclusion, recent experimental studies in clinical cases have clearly shown that drug resistance in Toxoplasma is ongoing. Thus, establish a more effective therapeutic scheme in the treatment of toxoplasmosis is critically needed. The emergence of T. gondii strains resistant to cur¬rent drugs, reviewed here, repre¬sents a concern not only for treatment failure but also for increased clinical severity in immunocompromised patients. To improve the therapeutic outcome in patients, development of a greater understanding of exact mechanisms of drug resistance in T. gondii is needed. Additionally, monitoring the presence of resistant parasites, in food products, would thus seem a prudent public health program.